2022
DOI: 10.3390/ijerph19073972
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Physical Activity and Psychological Distress in Patients Receiving Hemodialysis with Comorbidities: A Cross-Sectional Study

Abstract: Comorbidities cause psychological distress to patients on hemodialysis and cause their physical function to deteriorate. This study aims to examine whether physical patterns are associated with anxiety, depression and fatigue among patients with and without comorbidities who are on hemodialysis. To this end, a cross-sectional survey was administered to 120 patients on hemodialysis. Data were collected using the International Physical Activity Questionnaire—Short Form, Beck Depression Inventory—Second Edition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
5
1
Order By: Relevance
“…This finding is consistent with the results of Schouten et al’s [ 62 , 63 ] study of HD and peritoneal dialysis patients at 10 dialysis centers in the Netherlands with a mean anxiety level of 10.3 ± 10.1. However, our results were higher than those of Zhang et al [ 64 ], Kurtgoz et al [ 65 ], Zahedian et al [ 66 ], Cukor et al [ 46 ], Wu et al [ 67 ], and Nadort et al [ 47 ]. This inconsistency might be due to different countries, single- or multi-centers, eligible participants, with or without COVID-19 infection, and before or during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 87%
“…This finding is consistent with the results of Schouten et al’s [ 62 , 63 ] study of HD and peritoneal dialysis patients at 10 dialysis centers in the Netherlands with a mean anxiety level of 10.3 ± 10.1. However, our results were higher than those of Zhang et al [ 64 ], Kurtgoz et al [ 65 ], Zahedian et al [ 66 ], Cukor et al [ 46 ], Wu et al [ 67 ], and Nadort et al [ 47 ]. This inconsistency might be due to different countries, single- or multi-centers, eligible participants, with or without COVID-19 infection, and before or during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 87%
“…While undergoing treatment, MHD patients might experience both acute and chronic complications, which can cause intermittent or persistent physical discomfort and pain, which can lead to increased negative emotions [ 44 ]. The severity of these complications will affect the patient’s mental health both directly and indirectly [ 45 ]. Furthermore, studies have shown that an increased prevalence of complications is associated with a lower sense of well-being [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of these complications will affect the patient’s mental health both directly and indirectly [ 45 ]. Furthermore, studies have shown that an increased prevalence of complications is associated with a lower sense of well-being [ 45 , 46 ]. For example, patients with systemic itching tend to demonstrate more obvious characteristics of a state of negative emotion than those who do not experience systemic itching [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities are associated with the severity of depression, anxiety, and fatigue, which reduce the amount of physical activity in patients. This may decrease physical function, which in turn affect the degree of walking independence [ 38 ].The presence of comorbidities has received increasing attention worldwide [ 39 ] and should also be noted in patients undergoing dialysis induction.…”
Section: Discussionmentioning
confidence: 99%